Da inserção do critério da ambientalidade no simples nacional: um estímulo fiscal para a concretização do direito fundamental ao meio ambiente ecologicamente equilibrado - Garrido, Andre Viana (2017)
It intends to analyze in which perspectives the tax can be used as instrument of protection of an ecologically balanced environment. The human activities of industrial production in large scale often generates negative externalities in nonconformity with the precepts of sustainability. So, it seeks to verify how and in which measure it is possible to utilize the tax to intervene in the economics dominion and direct the producer agents to rule yours manufacturing processes since its beginnings on the ecologically balanced standards foreseen inside the model of the sustainable development. On the Brazilian Legal Order, two principles constitutes themselves as part of the foundation on which is built the national economic order: the defense of the environment including the offer of a differentiated juridical treatment according to the environmental impacts of the products and services, and its elaboration process and the provision of their services. Also, the differentiated juridical treatment, more profitable, offered to the micro enterprises and small business through the simplification of their administrative and tax obligations. The complementary law nº 123/2006 that institutes the “Estatuto Nacional da Microempresa e da Empresa de Pequeno Porte” (National Statute of the Micro Enterprises and Small Business) and also brings the “Regime Especial Unificado de Arrecadação de Tributos e Contribuições” (Unified Special Polity of Tax and Contribution Collection), as known as “Simples Nacional” (National Simple). It pretends, so, to investigate the possibility to give exemption (immunity) concessions of federal taxes, inside the “Simples Nacional” systematics, to those whom obey some environmental criteria of utilization of electrical energy, dispersion of pollutants in the atmosphere, and solid waste control of the entire production chain. Therefore, it intents to modify the Table II that predicts the tax incidences to the industrial sector, and to propose more profitable aliquots to those enterprises opting for the environmental way of production.